Analysis of Levi-Strauss's Structuralism on the Myth of Princess Mandalika - Suryadmaja, Galih; Utari, Retno; Haryono, Haryono; Ningsih, Dewi Puspita (Global Journal of Social Learning, 2025)
The myth of Princess Mandalika is a significant folktale within the culture of the Sasak people in West Nusa Tenggara, Indonesia. This myth illustrates the sacrifice of a princess for the sake of social harmony within her community, and it reflects profound cultural values. This study employs Claude Lévi-Strauss's structuralist approach to analyse the narrative structure and symbolic meanings within the myth of Princess  Mandalika. Through this analysis, the research aims to understand how the various elements of the myth interact to form a more complex meaning and reflect the duality of values in Sasak culture. The primary focuses of this research are: 1) to analyse the narrative structure of the myth of Princess  Mandalika, 2) to identify the symbolic meanings of the elements within the myth, and 3) to comprehend how this myth reflects the social values and cultural identity of the Sasak community. The analysis reveals that the myth embodies values of collectivism, sacrifice, and the relationship between humans and nature. The sea, as a symbol within the myth, represents uncertainty and the power of nature that must be respected. Furthermore, the sacrifice of Princess Mandalika illustrates a moral principle that emphasises the interests of the community over those of the individual. This study reveals that the myth of Princess Mandalika serves not only as a cultural narrative but also as a mirror of the social values that continue to shape the identity of the Sasak people to this day.